2015
DOI: 10.1021/jf505425d
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Phenolic Compounds Selectively Inhibit the Individual Subunits of Maltase-Glucoamylase and Sucrase-Isomaltase with the Potential of Modulating Glucose Release

Abstract: In this study, it was hypothesized that dietary phenolic compounds selectively inhibit the individual C- and N-terminal (Ct, Nt) subunits of the two small intestinal α-glucosidases, maltase-glucoamylase (MGAM) and sucrase-isomaltase (SI), for a modulated glycemic carbohydrate digestion. The inhibition by chlorogenic acid, caffeic acid, gallic acid, (+)-catechin, and (-)-epigallocatechin gallate (EGCG) on individual recombinant human Nt-MGAM and Nt-SI and on mouse Ct-MGAM and Ct-SI was assayed using maltose as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 54 publications
3
44
0
Order By: Relevance
“…maltase-glucoamylase (MGAM), sucrase-isomaltase (SIS), lactase (LCT), and trehalase (TREH) hydrolyze the disaccharides maltose, sucrose, lactose, and trehalose, respectively, to generate monosaccharides (16)(17)(18)(19). Here, we used PCR, in situ hybridization, and immunohistochemistry to determine that multiple sugar-and starchhydrolyzing enzymes are expressed in taste cells.…”
Section: Significancementioning
confidence: 99%
“…maltase-glucoamylase (MGAM), sucrase-isomaltase (SIS), lactase (LCT), and trehalase (TREH) hydrolyze the disaccharides maltose, sucrose, lactose, and trehalose, respectively, to generate monosaccharides (16)(17)(18)(19). Here, we used PCR, in situ hybridization, and immunohistochemistry to determine that multiple sugar-and starchhydrolyzing enzymes are expressed in taste cells.…”
Section: Significancementioning
confidence: 99%
“…Starting from the oral cavity, TPP inhibit the activities of alphaamylase and alpha-glucosidase, thereby hindering the digestion of carbohydrates. When passing through the digestive tract, TPP also inhibit the activities of maltogenic amylase and sucrase-isomaltase, and nutrient transporters in the small intestine, thereby reducing the carbohydrate absorption (Simsek, Quezada-Calvillo, Ferruzzi, Nichols, & Hamaker, 2015).…”
Section: B I Olog I C Al Fun C Ti On S Of Tppmentioning
confidence: 99%
“…Coffee contains chlorogenic acid, and green tea contains caffeic acid and catechins which are known a-glucosidase inhibitors (Adisakwattana et al 2009;Nguyen et al 2012). In a study by Simsek et al (Simsek et al 2015), chlorogenic acid, epigallocatechin gallate, (þ)-catechin, caffeic acid, and gallic acid were examined for their effect on the kinetics of maltose digestion and mechanism of inhibition against each a-glucosidase subunit. It was found that the inhibition constants (K i ) for epigallocatechin gallate against glucoamylase (1.7 ± 0.7 lM) and chlorogenic acid against sucrase (1.8 ± 0.3 lM) were the lowest compared to any other phenolics acting on any other subunits (Simsek et al 2015).…”
Section: Inhibition Of the A-glucosidasesmentioning
confidence: 99%
“…In a study by Simsek et al (Simsek et al 2015), chlorogenic acid, epigallocatechin gallate, (þ)-catechin, caffeic acid, and gallic acid were examined for their effect on the kinetics of maltose digestion and mechanism of inhibition against each a-glucosidase subunit. It was found that the inhibition constants (K i ) for epigallocatechin gallate against glucoamylase (1.7 ± 0.7 lM) and chlorogenic acid against sucrase (1.8 ± 0.3 lM) were the lowest compared to any other phenolics acting on any other subunits (Simsek et al 2015). Therefore, there is benefit in focusing further research on the effect of epigallocatechin gallate and chlorogenic acid on slowing the a-glucosidase C-terminal subunit digestion.…”
Section: Inhibition Of the A-glucosidasesmentioning
confidence: 99%